Modernidad, cultura de latifundio y cultura minoritaria en El lugar sin límites (1966) de José Donoso - Miriam Pino (Les Cahiers ALHIM)
The aim of this proposal is returning to one of the most important novels not only of Chilean literature, but also in Latin America. Extensive corpus donosiano, stands out for its richness and validity Place without limits, written and published in Mexico. The text refracts strong cores that articulate literature-society. Manuela González Astica transvestite history allows access mode on how to understand Latin America, heterogeneous and modernity rooted in not a few cases, in corporate enclaves where the culture of the latifundio combines patriarcado-sometimiento and gender. I consider this triad as a highly troubled unit that is recreated and questioned since the artistic productions. Place without limits was published during the boom of the so-called “Boom” of Latin American literature and was considered many times by critics only as an exercise in his later novel The obscene bird of the night. However, a deeper analysis allows us to conjecture that it is a key piece of Donoso through which it is possible to discern a critique of the modern Chilean State of the Decade of the sixties, stressing dimensions socio economic waste and acknowledge individuals 'out of place'.